A recessive genetic model and runs of homozygosity in major depressive disorder. Issue 2 (30th January 2014) - Power, Robert A.; Keller, Matthew C.; Ripke, Stephan; Abdellaoui, Abdel; Wray, Naomi R.; Sullivan, Patrick F.; ,; Breen, Gerome
<x xml:space="preserve">Abstract</x> Genome‐wide association studies (GWASs) of major depressive disorder (MDD) have yet to identify variants that surpass the threshold for genome‐wide significance. A recent study reported that runs of homozygosity (ROH) are associated with schizophrenia, reflecting a novel genetic risk factor resulting from increased parental relatedness and recessive genetic effects. Here, we explore the possibility of such a recessive model in MDD. In a sample of 9, 238 cases and 9, 521 controls reported in a recent mega‐analysis of 9 GWAS we perform an analysis of ROH and common variants under a recessive model. Since evidence for association with ROH could reflect a recessive mode of action at loci, we also conducted a genome‐wide association analyses under a recessive model. The genome‐wide association analysis using a recessive model found no significant associations. Our analysis of ROH suggested that there was significant heterogeneity of effect across studies in effect (P = 0.001), and it was associated with genotyping platform and country of origin. The results of the ROH analysis show that differences across studies can lead to conflicting systematic genome‐wide differences between cases and controls that are unaccounted for by traditional covariates. They highlight the sensitivity of the ROH method to spurious associations, and the need to carefully control for potential confounds in such analyses. We found no strong evidence for a recessive model underlying MDD. © 2014 Wiley Periodicals, Inc.